The general equation for a wave travelling in the +x direction is
y = Asin(wt - kx)

The general equation for a wave travelling in the -x direction is
y = -Asin(wt + kx)

These two waves give a standing wave equation of
y = -2Acos(wt)sin(kx)

In this case the standing wave is y = -6cos(6t)sin(4x)
so that A = 3, w = 6 and k = 4.
Thus the wave traveling in the +x direction (to the right) is the reflected wave:
y = 3sin(6t-4x)

And the wave traveling in the -x direction (to the left) is the incident wave:
y = -3sin(6t+4x)

Return to Self Test 5